2001
DOI: 10.1128/iai.69.8.5056-5063.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonsteroidal Anti-Inflammatory Drugs on Helicobacter pylori -Infected Gastric Mucosae of Mice: Apoptosis, Cell Proliferation, and Inflammatory Activity

Abstract: Helicobacter pylori and nonsteroidal anti-inflammatory drugs (NSAIDs) are two well-known important causative factors of gastric damage. While H. pylori increases apoptosis and the proliferation of gastric epithelial cells and is an important factor in peptic ulcer and gastric cancer, NSAIDs induce cell apoptosis and have antineoplastic effects. We investigated the effects of NSAIDs (a nonselective cyclooxygenase [COX] inhibitor [indomethacin] and a selective COX-2 inhibitor [NS-398]) on the apoptosis and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Helicobacter pylori infection is a major cause of chronic gastritis, peptic ulceration, and gastric carcinoma [3]. Studies have shown that COX-2 is induced in gastric mucosa during H. pylori infection [4][5][6] and that NSAIDs enhance H. pylori-induced gastric inflammation and ulceration [7][8][9][10][11][12]. However, the role played by COX-2 in H. pylori-induced gastric inflammation is not entirely understood.…”
mentioning
confidence: 99%
“…Helicobacter pylori infection is a major cause of chronic gastritis, peptic ulceration, and gastric carcinoma [3]. Studies have shown that COX-2 is induced in gastric mucosa during H. pylori infection [4][5][6] and that NSAIDs enhance H. pylori-induced gastric inflammation and ulceration [7][8][9][10][11][12]. However, the role played by COX-2 in H. pylori-induced gastric inflammation is not entirely understood.…”
mentioning
confidence: 99%
“…Risk of development and mortality from gastric cancer among nonsteroidal antiinflammatory drugs (NSAIDs; in here, as cyclooxygenase inhibitors) users also seems to be lower than among nonusers (5)(6)(7). Some studies have reported that NSAIDs have a protective role in patients with peptic ulcers, but others have shown elevation of the risk among NSAIDs users infected with H. pylori (8,9). NSAIDs are furthermore associated with serious upper gastrointestinal bleeding and cardiovascular events, and such harmful affects are a serious public health concern in American-European populations (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Of the three precancerous changes (atrophy, intestinal metaplasia and dysplasia), celecoxib was effective on the regression of dysplasia. However, the evidence for chemopreventive effects on gastric precancerous lesions by NSAIDs has only been limited to animal experiments [13,[17][18][19][20][21][22] . In the animal model of carcinogenesis induced by co-treatment with H pylori and N-methyl-N-nitrosourea (MNU), mice underwent H pylori-induced gastritis with multifocal atrophy and intestinal metaplasia, and finally gastric adenocarcinoma.…”
Section: Zhang Lj Et Al Celecoxib and Gastric Precancerous Lesionsmentioning
confidence: 99%